2007
DOI: 10.1111/j.1601-0825.2006.01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of BMP‐4 and Runx2 expression patterns in mouse temporomandibular joint after ovariectomy

Abstract: Estrogen plays important roles in the metabolism and maintenance of TMJ via regulations of signaling molecules such as BMP-4, Runx2, and BSP. Our results suggest that estrogen deficiency is a candidate cause of TMD. This study revealed further osteogenetic properties of estrogen that may be useful in the clinical treatment and prevention of TMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…A previous study 36 reported intense and moderate RANKL staining on osteoblasts and osteoclasts. Positive BSP staining was also previously reported 12 during the first week after ovariectomy and OCC expression was clearly changed by ovariectomy 37 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A previous study 36 reported intense and moderate RANKL staining on osteoblasts and osteoclasts. Positive BSP staining was also previously reported 12 during the first week after ovariectomy and OCC expression was clearly changed by ovariectomy 37 .…”
Section: Discussionmentioning
confidence: 62%
“…Studies have shown that ovariectomy induces bone loss in the whole mandible, including its condyle [7][8][9][10][11] . Structural defects in mandibular condyles were found in patients diagnosed with severe osteoporosis after menopause, indicating that osteoporosis can change mandibular condyle structure 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, estrogen negatively regulates condylar cartilage differentiation in vivo. In 4-month-old mice, ovariectomy has been shown to cause an increase in collagen type X expression after 1-8 weeks (18) . The ability of estrogen to decrease growth and differentiation of the mandibular condylar cartilage is consistent with the literature on growth plate cartilages; however, estrogen is believed to have a chondro-protective effect on articular cartilages.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of folding and the number of immunoreactive cells to iNOS, NF-κB, and PCNA in the synovial membranes is summarized in Table 1 and by utilizing the semi-quantitative scoring method (Kishimoto et al, 2007; Min et al, 2007). …”
Section: Resultsmentioning
confidence: 99%